The removal of information from working memory. Issue 1 (9th May 2018) - Lewis‐Peacock, Jarrod A.; Kessler, Yoav; Oberauer, Klaus
Abstract: What happens to goal‐relevant information in working memory after it is no longer needed? Here, we review evidence for a selective removal process that operates on outdated information to limit working memory load and hence facilitates the maintenance of goal‐relevant information. Removal alters the representations of irrelevant content so as to reduce access to it, thereby improving access to the remaining relevant content and also facilitating the encoding of new information. Both behavioral and neural evidence support the existence of a removal process that is separate from forgetting due to decay or interference. We discuss the potential mechanisms involved in removal and characterize the time course and duration of the process. In doing so, we propose the existence of two forms of removal: one is temporary, and reversible, which modifies working memory content without impacting content‐to‐context bindings, and another is permanent, which unbinds the content from its context in working memory (without necessarily impacting long‐term forgetting). Finally, we discuss limitations on removal and prescribe conditions for evaluating evidence for or against this process. Abstract : What happens to goal‐relevant information in working memory after it is no longer needed? Here, we review evidence for a selective removal process that operates on outdated information to limit working memory load and hence facilitates the maintenance of goal‐relevant information. We discuss the potential mechanisms involved in removal, as well as limitations on removal, and prescribe conditions for evaluating evidence for or against this process.